“Wriggling parasite inside the bladder” : case report in Semarang, Indonesia - Yohanes Dona Christi Utama; Dimas S. Wibisono; Yustina Elisa Febriany (Brawijaya Journal of Urology, 2021)
Introduction & Objectives: Finding "worm-like" parasite inside human bladder is rare. Most possible causes are parasitic helminths and myiasis. They may cause cystitis and/or urethritis symptoms : dysuria, haematuria, urethral discharge, and abdominal pain. The pathogenicity results from inflammation and toxin secreted by the larvae. Progressive and continuous bladder-wall necrosis may occur associated with larval growth and invasion. Knowing the causal parasite, its clinical manifestation, and the treatment is important to discuss. Material & Method: We present a case report of 60 years-old-man experiencing moving suprapubic pain for a month, especially when urinating (dysuria), and had pinkish urine color. Surprisingly, during performing cystoscopic and bladder evacuation, 2 mm-long worm-like pinkish-white moving object was found inside the bladder. Bloody urine sample was sent to the laboratory but no adequate larvae found in the urine. It made the parasitologists difficult to mention what was the exact species of the larvae. There were pinkish color, microhematuria, and no suspected helminth’s eggs found from urinanalysis. The patient showed better improvements after surgery. His complaints gradually reduced, there was no more hematuria and dysuria. Discussion: Urinary helminth infection leads to permanent urogenital problems, renal failure and malignancy. Echinococcosis creates cysts, Filariasis involves lymphatic system obstruction. Helminths lay their eggs inside the urinary organs and excrete them through urine. These characteristics were not found in this case. Myiasis was more relevant with the involvement of worm-like creature. Microhematuria was found on laboratory examination. Major symptoms were moving abdominal pain with no exact location and pinkish urine. Recommended treatment was to remove the larvae and treat associated infection with antibiotics. Afterwards, there was significant improvement from the patient’s condition. Conclusion: Knowing the urinary tract parasite is important for its treatment. Further studies to analyze the larvae, prevent its infection, and decide the best treatment are necessary.